Increased cardiovascular mortality associated with gout: a systematic review and meta-analysis. (March 2015) - Clarson, LE; Chandratre, P; Hider, SL; Belcher, J; Heneghan, C; Roddy, E; Mallen, CD
Background: Hyperuricaemia, the biochemical precursor to gout, has been shown to be an independent risk factor for mortality from cardiovascular disease (CVD), although studies examining the clinical phenomenon of gout and risk of CVD mortality report conflicting results. This study aimed to produce a pooled estimate of risk of mortality from cardiovascular disease in patients with gout. Design: Systematic review and meta-analysis. Methods: Electronic bibliographic databases were searched from inception to November 2012, with results reviewed by two independent reviewers. Studies were included if they reported data on CVD mortality in adults with gout who were free of CVD at time of entry into the study. Pooled hazard ratios (HRs) for this association were calculated both unadjusted and adjusted for traditional vascular risk factors. Results: Six papers, including 223, 448 patients, were eligible for inclusion (all (CVD) mortality n  = 4, coronary heart disease (CHD) mortality n  = 3, and myocardial infarction mortality n  = 3). Gout was associated with an excess risk of CVD mortality (unadjusted HR 1.51 (95% confidence interval, CI, 1.17–1.84)) and CHD mortality (unadjusted HR 1.59, 95% CI 1.25–1.94)). After adjusting for traditional vascular risk factors, the pooled HR for both CVD mortality (HR 1.29, 95% CI 1.14–1.44) and CHD mortality (HR 1.42, 95% CI 1.22–1.63) remained statistically significant, but none of the studies reported a significant association with myocardial infarction. Conclusions: Gout increases the risk of mortality from CVD and CHD, but not myocardial infarction, independently of vascular risk factors.